AB1052 Revisiting chemical and morphological diversity of calcium-containing crystals in human osteoarthritic menisci. (23rd January 2014) - Nguyen, C.; Lioté, F.; Hannouche, D.; Bousson, V.; Velard, F.; Daudon, M.; Bazin, D.; Ea, H.-K.
Abstract : Background: Calcium-containing crystals (CC), including basic calcium phosphate crystals (BCPs) and calcium pyrophosphate crystals (CPPs) are associated with destructive forms of osteoarthritis (OA). Recent reports support that mineralization of several joint structures, including articular cartilage and menisci, is an indissociable process of end-stage OA. Objectives: To assess prevalence and biochemical composition of mineral phases in human OA menisci, and to determine their morphological aspects. Methods: Fourteen patients (12 females and 2 males) who underwent total knee replacement (TKR) surgery for primary OA were prospectively included. A 24-year-old woman who underwent TKR for chondrosarcoma, and a 28-year-old man who had meniscectomy for medial meniscus tear served as non-OA control subjects. Clinical data and preoperative knee plain radiographs were retrieved from clinical charts. Specimen included lateral meniscus and medial meniscus, when this latter was available. For each meniscus, 2 samples were collected, consisting in 1-mm-thick slices. Slices were cut tangentially to the surface of the meniscus center part, within its superficial and deep layers, respectively. Menisci calcifications prevalence and semi-quantification were obtained using digital contact radiography (DCR). Biochemical composition was assessed using Fourier-transform infra-red (FTIR), while morphological aspects were determined using scanning electron microscopy (SEM). Results: Mean age and body mass index at the time of TKR were 73.7 (8.6) years, and 29.3 (7.4) kg/m 2, respectively. Preoperative X-rays, available for 9 patients, found uni-, bi- or tricompartmental knee OA in 3 (33.3%), 5 (55.5%) and 1 (11.1%) cases, respectively. In all cases, the compartment mainly affected was medial femoro-tibial, and mean Kellgren and Lawrence score was 3.7±0.5. Overall, 19 menisci (14 lateral and 5 medial) were harvested and analysed. Visual assessment found macroscopic menisci calcifications in 10 OA out of 14 patients (71.4%). Using DCR, CC were detected in all 19 OA menisci, whereas CC were not detected in non-OA control menisci. The mean overall mineral content represented 9.0±5.3% of total volume (range 3.2-24%). FTIR analysis confirmed the presence CC in all 19 OA menisci specimens. CC were identified as CPPs only in 10 menisci (52.6%), as BCPs only in 6 (31.6%) and as both BCPs and CCPs in 3 (5.2%). Mean overall CPPs content represented 12.1±16.3% and mean overall BCPs content represented 2.9±5.4%. In all cases, identified BCPs were characterized as carbonated apatite. Finally, by SEM, 2 different morphological aspects were identified: 1) spherical structures, typical of biological apatite, resulting from an agglomeration of nm-scale cristallites surrounded by proteins, in the BCPs-containing samples; 2) acicular or cubic structures of different sizes, in the CPPs-containing samples. Conclusions: CC are constantly found in human OA menisci at the time of knee joint replacement. Cartilage calcifications in human OA menisci are mainly identified as CPPs. Furthermore, CC morphological aspects are specific to the crystal type. Disclosure of Interest: None Declared